Peran Tumor Necrosis Factor-Alpha Sistemik pada Respons Imun Toksoplasmosis Okuler - Wahyudi, I Nyoman Surya Ari; Sofia, Ovi (PT Kalbe Farma Tbk., 2025)
Ocular toxoplasmosis (OT) is the most common infection causing posterior uveitis worldwide, caused by the parasite Toxoplasma gondii. Many cytokines such as TNF α, IL-6, and IL-10 are involved in the development of uveitis. Tumor necrosis factor (TNF) is a pro-inflammatory cytokine released primarily during inflammatory response of macrophages and T cells, to mediate the activation and infiltration of leukocytes and T helper (Th)1 lymphocyte responses in the tissue. Macular inflammation caused by TO can lead to substantial visual impairment. High level of TNF-α cause disruption of the blood-retinal barrier in uveitis. TNF-α plays a role as a positive regulator of the immune response. Systemic TNF-α levels in ocular infections, particularly TO, increase, which is associated with an increased inflammatory response, contributing to choroidal and retinal tissue damage in TO patients. The TNF-α levels in tissues and intraocular fluid can vary depending on the type and severity of infection. Detection of systemic TNF-α may act a potential clinical biomarker for ocular toxoplasmosis.